Health literacy and medication adherence in adults from ethnic minority backgrounds with Type 2 Diabetes Mellitus: a systematic review - Jinal Parmar; Aymen El Masri; Freya MacMillan; Kirsten McCaffery; Amit Arora (BMC Public Health)
Abstract Background For people living with Type 2 Diabetes Mellitus (T2DM), achieving optimal health outcomes requires optimal self-management and adherence to medical treatment. While some studies suggest an association between poor medication adherence and lower levels of health literacy, the evidence for this association remains inconclusive. This systematic review aimed to synthesise the evidence on the association between health literacy and medication adherence among adults from ethnic minority backgrounds living with T2DM. Methods Medline (Ovid), The Cochrane Library, Embase (Ovid), PsycInfo (EBSCO), and the Cumulative Index to Nursing and Allied Health Literature (CINAHL) (EBSCO) were searched systematically for peer-reviewed literature, published until January 2024. Studies were included in this review if they assessed health literacy and medication adherence among ethnic minority people with T2DM. Two reviewers independently screened and selected the studies, extracted data from the included articles, and assessed the methodological quality of the studies. The methodological quality and bias in designing, conducting, and analysis of each study were evaluated using a standardised JBI critical appraisal tool. Results Of the total 6,318 identified studies, seven studies were included in the review. The total participant sample sizes across these studies varied from 53 to 408 participants. All included studies incorporated cross-sectional design for the research, with the majority conducted in the USA. Of the seven unique studies, only one study observed a significant association between health literacy and medication adherence among people from an ethnic minority background. Conclusions Evidence on the association between health literacy and medication adherence in ethnic minority adults with T2DM is weak and inconsistent. To understand this association more clearly in ethnic minority populations and to address the disparities in cultural and linguistic considerations, well-designed studies are required. Trial registration This review is registered with PROSPERO (CRD42022328346).